A Glycosylphosphatidylinositol-Anchored α-Amylase Encoded by amyD Contributes to a Decrease in the Molecular Mass of Cell Wall α-1,3-Glucan in Aspergillus nidulans - Miyazawa, Ken; Yamashita, Takaaki; Takeuchi, Ayumu; Kamachi, Yuka; Yoshimi, Akira; Tashiro, Yuto; Koizumi, Ami; Ogata, Makoto; Yano, Shigekazu; Kasahara, Shin; Sano, Motoaki; Yamagata, Youhei; et al. (Frontiers in Fungal Biology, 2022)
α-1,3-Glucan is one of the main polysaccharides in the cell wall of Aspergillus nidulans. We previously revealed that it plays a role in hyphal aggregation in liquid culture, and that its molecular mass (MM) in an agsA-overexpressing (agsAOE) strain was larger than that in an agsB-overexpressing (agsBOE) strain. The mechanism that regulates its MM is poorly understood. Although the gene amyD, which encodes glycosylphosphatidylinositol (GPI)-anchored α-amylase (AmyD), is involved in the biosynthesis of α-1,3-glucan in A. nidulans, how it regulates this biosynthesis remains unclear. Here we constructed strains with disrupted amyD (ΔamyD) or overexpressed amyD (amyDOE) in the genetic background of the ABPU1 (wild-type), agsAOE, or agsBOE strain, and characterized the chemical structure of α-1,3-glucans in the cell wall of each strain, focusing on their MM. The MM of α-1,3-glucan from the agsBOEamyDOE strain was smaller than that in the parental agsBOE strain. In addition, the MM of α-1,3-glucan from the agsAOE ΔamyD strain was greater than that in the agsAOE strain. These results suggest that AmyD is involved in decreasing the MM of α-1,3-glucan. We also found that the C-terminal GPI-anchoring region is important for these functions.